Awareness of Generation Z Students about The Plaf (Plastic Flamingo) and Other Campaigns Concerning Plastics in Online Shopping - Mary Grace C. Manucom; Kimberly P. Alcaraz; Rica Pearl S. Alejo; Karen Celine M. Gaddi; Kate Eleonore P. Recio; Reika G. Yamaguchi (International Journal of Environment, Engineering and Education, 2023)
Environmental awareness is crucial in addressing the issues of plastic waste and pollution, which have a significant impact on our environment and our health. The study aimed to analyze the awareness of Bulacan State University College of Science Generation Z students regarding PLAF (Plastic Flamingo) and other campaigns related to plastics in online shopping. The researchers used a descriptive research design to achieve this goal and collected data from 350 samples of Generation Z students through a standardized questionnaire distributed via Google Forms. The findings revealed that Shopee is the most commonly used online shopping application by students, and they tend to purchase items online when needed. Bubble wrap emerged as the most frequently used parcel packaging material. The results also indicated that the students are highly aware of the different impacts of parcel packaging, as evidenced by the mean score of 4.02. However, their awareness of environmental campaigns related to plastic was only average, with a mean score of 2.93. In particular, the understanding of PLAF (Plastic Flamingo) was low, with a cumulative mean score of 2.13. The findings suggest the need to improve Generation Z students' awareness of environmental campaigns and promote ecological practices and involvement in addressing plastic waste and pollution issues. Educating and engaging students through various campaigns and initiatives can help raise their awareness of the environmental impacts of plastic waste and encourage them to adopt sustainable practices in their daily lives.